ANALISIS KEMUDAHAN SISTEM INFORMASI DIGITAL DALAM MENINGKATKAN PENGAMBILAN KEPUTUSAN MANAJERIAL PERSPEKTIF AKUNTANSI MANAJEMEN PADA PT. PEGADAIAN CABANG BULUKUMBA - Nur Anisa Putri; Masrullah; Wahyuni (STKIP Subang, 2026)
This study aims to analyze the ease of use of digital information systems in supporting managerial decision-making at PT. Pegadaian Bulukumba Branch from a management accounting perspective. The use of information technology is considered important for producing fast, precise, and accurate decisions. The method used is descriptive qualitative with interview, observation, and documentation techniques. Research informants include leaders, employees, and customers who are directly involved in the use of digital systems. Data were analyzed through data reduction, data presentation, and conclusion drawing. The results of the study indicate that the ease of use of digital information systems contributes to the effectiveness of managerial decision-making. This can be seen from the easily accessible and accurate system that simplifies information analysis, and supports planning, control, and evaluation of company performance.